2009
DOI: 10.1007/s00204-009-0505-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of selenium genotoxic, cytotoxic, and protective effects: a review

Abstract: Selenium is an oligoelement with essential biological functions. Diet is the most important selenium source, and intake of this element depends on its concentration in food and amount of food consumed. Among the essential human micronutrients, selenium is peculiar due to its beneficial physiological activity and toxicity. It may have anticarcinogenic effects at low concentrations, whereas at concentrations higher than those necessary for nutrition, it can be genotoxic and carcinogenic. Because of that, seleniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(99 citation statements)
references
References 135 publications
3
94
0
2
Order By: Relevance
“…Selenium deficiency has now been recognized as a global problem which needs to be addressed (Valdiglesias et al 2010). The role of selenium for maintenance of health and the prevention of several diseases is probably more important than it was realised until now (Clark et al 1996;Ip 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Selenium deficiency has now been recognized as a global problem which needs to be addressed (Valdiglesias et al 2010). The role of selenium for maintenance of health and the prevention of several diseases is probably more important than it was realised until now (Clark et al 1996;Ip 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the toxicities of supranutritional doses of the different Se compounds in clinical use have not been systematically evaluated. Of particular concern is the genotoxicity of some forms of Se, particularly the inorganic salts (14), and the possibility that using these in conjunction with other genotoxic therapies (such as radiation and alkylating agents) could increase the risk of second malignancies and myelodysplasia. No clinical trials to date have reported on such end-points.…”
Section: Abstract Selenium Is An Essential Trace Element Involved Inmentioning
confidence: 99%
“…Animal laboratory studies have shown that the organic forms of Se are both more effective and safer than the commonly-used inorganic forms such as sodium selenite (SS), which are more genotoxic (14). From 50% lethal dose (LD 50 ) determinations, SS was found to be fourfold more toxic than SLM when administered to mice intravenously and three-fold more toxic than Se-yeast when given orally to rats (17).…”
Section: Selenium Compounds -Metabolism Pharmacology and Toxicitymentioning
confidence: 99%
“…However, at concentrations higher than needed for nutrition, selenium proves to be genotoxic and carcinogenic. This study may help regulate the use of selenium in nutrition (6) Valdiglesias et al (2010) Silver nanoparticles (AgNPs) caused a concentration-dependent increase in reactive oxygen species (ROS), mitochondrial damage, DNA adducts and apoptosis in a human alveolar cell line. Pre-treatment with antioxidants reduced ROS as well as DNA adducts underlining the relevance of ROS in toxicity of AgNPs.…”
mentioning
confidence: 99%